Kekerasan Verbal pada Anak - Bonita Mahmud (Institut Agama Islam Negeri (IAIN) Bone-Indonesia, 2019)
Verbal Violence in ChildrenThe article describes verbal abuse in children. This is a result from review of related literature on verbal abuse against children. Everyone must understand the forms of verbal abuse against children, the influence factor, its impact on the child's growth and development, and the preventing efforts.Â AbstrakArtikel ini menjelaskan pelecehan verbal pada anak-anak. Ini adalah hasil dari tinjauan literatur terkait tentang pelecehan verbal terhadap anak-anak. Setiap orang harus memahami bentuk-bentuk pelecehan verbal terhadap anak-anak, faktor pengaruhnya, dampaknya pada pertumbuhan dan perkembangan anak, dan upaya pencegahannya.